Dampak Pembangunan Kawasan Industri di Kabupaten Semarang Terhadap Pekerja Wanita : Studi Kasus PT. Ungaran Sari Garmen - Rizqy Arief Wisdiawan; Turtiantoro .; Sulistyowati . (Journal of Politic and Government Studies, 2014)
This study analyzed the number of industries , especially those engaged in the field of garment that are emerging and growing in Kab. Semarang industry district. The number of industrial companies that grow and flourish in the Kab. Semarang has a very large number of workers to be employed in the production process . Seeing the number of workers employed by the dominance of female labor is then raises a question , how is the company 's in the garment Kab. Semarang to employ more women than men ? , But it also impacts among female workers who work and other impacts of the presence of the industrial area . Impact on women workers and people who work in the industrial area that is able to split my time between family , community and social environment around them In this study , researchersused a qualitative approach that will generate descriptive data . This research was conducted in Semarang regency , Central Java . The data in this study was obtained through interviews , observation , and documentation . The key informant interviews were conducted by female workers who are working in PT . Unggaran Sari Garmen , exposure of the company HDR , DINSOSNAKERTRANS as the party of government regulations governing the company with its workforce and the general public . While the documentation of data obtained from personal documentation taken around the industrial area , and is equipped documentation Semarang District Central Bureau of Statistics . The company employs more women in the production process because of the reason that women workers working more thorough, diligent , diligent , deft , and it is not owned by the labor of men , . Another impact to the surrounding community is the number of people around who use land around the industrial area to trading activity , transportation activity , making boarding building for many workers and surrounding communities are employed in the garmen industry is thus indirectly also reduce the unemployment rate in the Kab. Semarang. The existence of this industry region also makes the biggest contributor to revenue in the Kab. Semarang is then in one after another in the agricultural sector . The impact of such congestion around the existing industrial area , ranging loss of customs that place is replaced by migrants make one of the negative impacts of the industrial area.